Model Pembelajaran Bola Basket Melalui Permainan Basket Drum Dalam Pendidikan Jasmani Pada Siswa Kelas VIII SMP - Lalu Suharta (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study was to determine the development of the basketball learning model through basketball drum games in penjas for class VIII SMP N 1 Pujut, Pujut sub-district, Central Lombok Regency. The research method uses development research including field observations, interviews and literature studies, data in the form of results of assessment of product quality, and results of filling out questionnaires by students. The trial data obtained expert evaluation data, namely penjas expert 81.3% (good), learning experts I 93.3% (very good), expert learning II 84.4% (good), small group trials 79.1% ( good), and field test 81.4% (good).From the results above, it can be concluded that the learning model of the basketball drum game in Penjas for Grade VIII students of SMP N 1 Pujut, Pujut District, Central Lombok Regency can be used. Modified basketball game learning models can be accepted and implemented in the physical education learning process for class VIII students of Pujut 1 Junior High School.